Risk Factor Analysis of the Incidence of Hepatitis A in Indonesia: A Meta-Analysis - Cahyono, Yoyon Hariadi; Azizah, R.; Martini, Santi; Sulistyorini, Lilis (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Hepatitis transmission is still a global public health issue, including in Indonesia. Low personal hygiene and environmental sanitation are the contributing factors to hepatitis A. This study aimed to analyze the impact of hand-washing habits, cutlery exchange, food and snack hygiene, and latrine use on the incidence of Hepatitis A. The study used meta-analysis with the PICOS technique. The data from Google Scholar, Mendeley, and Research Gate by looking at keywords such as “risk factors” and “hepatitis A”, which were then sorted according to the inclusion-exclusion criteria and obtained 16 full-text case-control articles. Data analysis used a fixed effect model through JASP software version 0.9.2. The meta-analysis found that hand-washing behavior had a risk of 1.131; food and snack hygiene had a risk of 6.233; the habit of exchanging cutlery had a risk of 10.17; and latrine utilization had the highest risk of 12.935 for the incidence of hepatitis A. The study found that the use of latrines is the most significant factor in the occurrence of hepatitis A due to open defecation. Furthermore, exchanging cutleries is rated as the second factor triggering hepatitis A transmission, followed by the consumption of snacks or other foods. The study also found that hand-washing behavior has the lowest risk of hepatitis A incidence. The study concludes that hand-washing behavior, latrine utilization, food and snack hygiene, and exchanges of cutlery increase the risk of hepatitis A at different levels. It is suggested that behavioral factors such as hand washing, the use of closed latrines, and the consumption of healthy snacks or foods are essential measures to educate the community about hepatitis A and reduce its transmission within the population.